Comparing the effect of rhythmic stabilization and combination of isotonic technique on grip strength, pinch strength and dexterity of hand among middle aged healthy individuals - a randomized clinical trial - Sanjiv Kumar; Apoorva Dattatray Nale (H.S. Skovoroda Kharkiv National Pedagogical University, 2023)
Purpose: The aim of the study was to evaluate and compare the effects of Rhythmic Stabilization and a combination of isotonic technique on grip  strength, pinch strength, and dexterity of hand among middle aged healthy individuals. Methods Forty middle aged healthy individuals were selected on the basis of inclusion and exclusion criteria. Participants were randomly allocated to two groups, with 20 in group A (Rhythmic Stabilization) and 20 in group B (Combination of Isotonic Technique). Treatment was given for 4 weeks, thrice a week. Outcome measures: grip strength, pinch strength, and dexterity were assessed by the Jamar hand dynamometer, the Pinch gauge, and the Perdue peg board, respectively. Outcome measures were assessed at baseline and after 4 weeks of treatment. Results Notably, Group A participants showed a significant improvement in all outcome measures compared to Group B (p<0.05) when compared. Both the interventions were effective for dexterity outcome in both groups (p<0.05).  Conclusion: This study provides evidence that application of Rhythmic Stabilization improves grip strength and pinch strength.  This suggests that static Proprioceptive Neuromuscular Facilitation (PNF) exercises performed on the fingers can improve dexterity, grip strength, and pinch strength in the middle-aged population. Highlights As age increases, there is decrease in grip strength and dexterity of a person. The grip strength, finger strength and dexterity are inter-related. The Proprioceptive Neuromuscular Facilitation increases strength of muscles. The static PNF exercises are more effective than the dynamic PNF exercises to improve strength of grip strength, finger strength and dexterity.